Association between hydration status, hydration knowledge and fluid consumption during training among soccer players - N. Jusoh; S. Salim (Physical Education of Students, 2018)
Study Aim: The purpose of this study was to determine the correlation between hydration status, knowledge of hydration and the amount of fluid intake consumption during training among the soccer players. Material and Methods: Pre-training hydration status was measured by urine colour chart and Urine Specific Gravity (USG). A questionnaire on hydration knowledge was answered by the participants on the last day of training session. Pearson Correlation test was used to analyse the correlation between hydration status, knowledge of hydration and total amount of fluid intake among the participants. Results: The results showed that the participants were dehydrated during the three days of training. Sixty four percent of the participants had a satisfactory knowledge of hydration. However, the results indicated that the sweat loss was higher than fluid intake during the training. Pearson test revealed there were positive correlation between USG and urine colour (r=0.809, p<0.001) as well as urine colour and fluid intake (r = .424, p<0.05). Conclusions: In conclusion, the findings indicate the needs to increase awareness of pre training hydration status among the participants.